Precision nutrition in the life style medicine times: Nutrición de precisión en los tiempos de la medicina del estilo de vida - Gallo, Aly (2019)
The etymological origin of the term Diet, derives from the Greek δίαιτα, understood as "lifestyle"; currently the Science shows that prevention and protection of well-being begin in the diet and continue in our Lifestyle. Diet is a key factor for the health status of the individual since the interaction between diet, environmental factors and genes, determines the well-being of people. The negative impacts on health, caused by an inadequate diet, are increasing every day. The obesity, the main consequence of this nutritional alteration, is one of the main causes of morbidity and mortality in most countries for the diseases associated with it, NTCDs (Non Transmissible Chronic Disease): dyslipidemias, cardiovascular diseases, diabetes mellitus type 2, fatty liver not alcoholic and even Cancer.